Herpetological phylogeographic analyses support a Miocene focal point of Himalayan uplift and biological diversification. Issue 9 (21st October 2020) - Xu, Wei; Dong, Wen-Jie; Fu, Ting-Ting; Gao, Wei; Lu, Chen-Qi; Yan, Fang; Wu, Yun-He; Jiang, Ke; Jin, Jie-Qiong; Chen, Hong-Man; Zhang, Ya-Ping; Hillis, David M; et al.
Abstract: The Himalaya are among the youngest and highest mountains in the world, but the exact timing of their uplift and origins of their biodiversity are still in debate. The Himalayan region is a relatively small area but with exceptional diversity and endemism. One common hypothesis to explain the rich montane diversity is uplift-driven diversification—that orogeny creates conditions favoring rapid in situ speciation of resident lineages. We test this hypothesis in the Himalayan region using amphibians and reptiles, two environmentally sensitive vertebrate groups. In addition, analysis of diversification of the herpetofauna provides an independent source of information to test competing geological hypotheses of Himalayan orogenesis. We conclude that the origins of the Himalayan herpetofauna date to the early Paleocene, but that diversification of most groups was concentrated in the Miocene. There was an increase in both rates and modes of diversification during the early to middle Miocene, together with regional interchange (dispersal) between the Himalaya and adjacent regions. Our analyses support a recently proposed stepwise geological model of Himalayan uplift beginning in the Paleocene, with a subsequent rapid increase of uplifting during the Miocene, finally giving rise to the intensification of the modern South Asian Monsoon.